Allotransplantasi Testis Mencit Muda sebagai Upaya Preservasi Gonad In Vivo - Wahono Esthi Prasetyaningtyas; Kusdiantoro Mohamad; Mokhamad Fahrudin; Ita Djuwita; Srihadi Agungpriyono (Institut Pertanian Bogor, 2007)
Cancer disease are not detected only at adult but also at young age. One therapy for cancer diseases is chemotherapy and radiation, that give a side effect of infertility in the gonad, therefore, it is necessary to preserve the gonad. Sperm collection from adult is easy but not from the young patients.Keyword: transpalantation, testis, mencit muda, spermatogenesis